CORAL REEF CONSERVATION INDEX IN SAMALONA ISLAND, CITY OF MAKASSAR - Pangadongan, Aksel Willyam Reynaldi; Chair Rani; Abdul Rasyid J (Jurnal Ilmu Kelautan SPERMONDE, 2025)
This study sought to evaluate the quality of benthic organisms and coral fish, as well as analyze the coral reef conservation index in the waters surrounding Samalona Island. The research was conducted in the northern, southern, and western waters of Samalona Island, encompassing five reef zones: reef flat, reef crest, upper and lower reef slopes, and reef base. The line intercept transect (LIT) method was employed in conjunction with the belt transect for the collection of benthic data, while the underwater visual census (UVC) was utilized for capturing reef fish data. Further assessments of the quality of benthic organisms and reef fish were conducted using the suspension technique outlined by McMellor (2007). The findings indicated that the quality of coral reef organisms on Samalona Island was suboptimal, with scores of 21, 19, and 28 for the southern, western, and northern sides, respectively. The quality of reef fish was categorized as moderate-low, with scores of 27, 31, and 33 on the southern, western, and northern sides of the island, respectively. Consequently, the coral reefs in the waters surrounding Samalona Island were evaluated using the D3–D4 conservation index for both the southern and western sides of the island. Although the northern side has a conservation index of E3 and includes degraded habitat, it is not recommended for designation as a conservation area.